The snack thief - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2005)
Suspecting a link between the murder of an elderly man and the shooting of an Italian fisherman, Inspector Montalbano encounters impoverished housekeeper and sometime prostitute Karima, whose thieving young son's life is endangered after she disappears.